2000
DOI: 10.1139/cjpp-78-8-603
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the large-scale geometry of human coronary arteries

Abstract: Abstract:Two principles suffice to model the large-scale geometry of normal human coronary arterial networks. The first principle states that artery diameters are set to minimize the power required to distribute blood through the network. The second principle states that arterial tree geometries are set to globally minimize the lumen volume. Given only the coordinates of an arterial tree's source and "leaves", the model predicts the nature of the network connecting the source to the leaves. Measurements were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Motivated by Murray’s law, a mathematical relationship between vessel size and flow, an area-based approach was used to assign capacitance and resistance values at the outlets. Capacitance values were chosen to be proportional to outlet area, and resistances values were determined according to a modified Murray’s law using an exponent of 2.0 for the aortic branches and 2.6 for the coronary branches [27, 28]. The equations governing the LPN, and methods for their solution, follow our previous work [24].…”
Section: Methodsmentioning
confidence: 99%
“…Motivated by Murray’s law, a mathematical relationship between vessel size and flow, an area-based approach was used to assign capacitance and resistance values at the outlets. Capacitance values were chosen to be proportional to outlet area, and resistances values were determined according to a modified Murray’s law using an exponent of 2.0 for the aortic branches and 2.6 for the coronary branches [27, 28]. The equations governing the LPN, and methods for their solution, follow our previous work [24].…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies reported morphometry exponents for the LCA ranging from 2.45 to 2.51 69 and m = 2.6 ± 0.64 for LCA in. 70 The total resistance of the downstream vasculature has been determined using various exponents m in coronary hemodynamics literature. Coronary models in Sankaran et al 55 assumed that the resistance is inversely proportional to the area of the distal branch with m = 2.…”
Section: Uncertainty In the Morphometry Exponentmentioning
confidence: 99%
“…29 Hypothetically, the optimal retinal vasculature will deliver the most efficient blood flow, whereby deviations or alterations from the optimal architecture are thought to result in impaired microcirculatory transport, increased shear stress, reduced efficiency, and hence a greater risk of vascular damage. [29][30][31] With state-of-the-art technology in retinal photography and computing image processing techniques, new computer-based programs were developed to perform objective and quantitative assessments of novel classes of retinal vascular parameters to reliably and rapidly quantify the geometric branching network, such as tortuosity, fractal dimension, and branching. These new retinal features capture the "optimality" of blood distribution in the retinal network that reflect the integrity of the cerebral microcirculation.…”
Section: Global Geometrical Patterns In Retinal Vasculaturementioning
confidence: 99%